The impact of operational risks in electronic banking In the light of the principles of Basel (II): An Empirical Study in some Iraqi banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Banks represents financial institutions that influence the economy of any country and their evolution and development is the need to seek all states , communities, maintain and control a guarantee of the beneficiaries investors and to promote confidence, so the specialized organizations trying to set principles and rules must be adhered to and are Basel (II) of the necessary effects to be introduced and work on their application.  Banks exposed by various risks one of them operational risks that have multiple effects on the activity of the institution itself, as well as the national economy, so this study was to find out what those effects and to find solutions and appropriate proposals to avoid Iraqi banks from the effects of risk, has been the adoption of the statistical analysis of data obtained them through the questionnaire that was distributed to a number of Iraqi, governments and private banks.              The study found multiple results, including how to create systems of internal control and external help in the application of Basel (II).